Influência da velocidade de varredura no comportamento em abrasão a três corpos de aço ferramenta refundido superficialmente por laser - Nascimento, Paulo Eustáquio Resende (1998)
Quenched and tempered AISI 420 Steel samples were surface remelted using an axial flux CO2 laser with 4 different scanning speeds in the 5 to 20 mm/s range. After microstructural characterization, the remelted layers were submitted to three bodies abrasion tests, using standard brazilian sand as abrasive material and an apparent pressure of 0,10 N/mm2 The effect of heat treatments ( quenching + tempering and subzero), carried out after laser surface melting, on the abrasion behaviour of the modified layers has also been analysed. It could be noticed that as scanning speed increases, reduce both the thictness of the remelted layer and the wear rate. This reduction in wear rate was more significant in the samples that was submitted to later heat treating, specially subzero quenching.